Electronic and structural properties of doped amorphous and nanocrystalline silicon deposited at low substrate temperatures by radio-frequency plasma-enhanced chemical vapor deposition - Alpuim, P. (2003)
The gas phase doping of hydrogenated amorphous silicon and hydrogenated nanocrystalline silicon thin films deposited on glass and on plastic (polyethylene terephthalate) substrates is reported. Two substrate temperatures were used during deposition: 25 degreesC and 100 degreesC. Films were deposited by radio-frequency plasma-enhanced chemical vapor deposition using phosphine or diborane for n- or p-type doping, respectively. Similar electronic and structural properties are obtained for the doped films deposited on either substrate. Hydrogen dilution of silane is used to improve the electronic and structural properties of the amorphous films and to obtain nanocrystalline films. The most conductive amorphous films have n-type dark conductivity at room temperature similar to10(-3) Omega(-1) cm(-1) and similar to10(-5) Omega(-1) cm(-1) when deposited at 100degreesC and 25degreesC, respectively, or p-type room-temperature dark conductivity similar to10(-7) Omega(-1) cm(-1) at both substrate temperatures. The most conductive nanocrystalline films deposited at 100 degreesC have n- and p-type dark conductivity at room temperature above 10(-2) Omega(-1) cm(-1) while nanocrystalline films deposited at 25 degreesC only have p-type conductivity higher than 10(-2) Omega(-1) cm(-1) at room temperature. Isochronal annealing at temperatures up to 300 degreesC showed that the dopants are fully activated at the deposition temperature in doped nanocrystalline samples and that they are only partially activated in amorphous films deposited at low substrate temperatures.